2017
DOI: 10.1017/s1755773917000078
|View full text |Cite
|
Sign up to set email alerts
|

One concept, many interpretations: the media’s causal roles in political agenda-setting processes

Abstract: While political agenda-setting scholars agree that the news media matter when it comes to agenda setting, surprisingly, there is no consensus on the exact role these media play in the agenda-setting process. In particular, causal interpretations of the media's role are diverse. This contribution focuses on this ambiguity in the agenda-setting field. First, it outlines the main reasons for the disagreement, both on a theoretical and on an empirical level. Second, it develops a theoretical model that helps to sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 82 publications
0
11
0
Order By: Relevance
“…For these elites, this was not “news,” there was no revelation from the media coverage (cf. Sevenans 2018). But the early coverage by The Guardian was important as a signal of a window of opportunity, and so was the attention and re-framing of the issue enabled by the digital petitions gathered by actors and technical artifacts in the campaign assemblage, including crowdsourced leaders (Papacharissi and de Fatima Oliveira 2012) and hybrid advocacy organizations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For these elites, this was not “news,” there was no revelation from the media coverage (cf. Sevenans 2018). But the early coverage by The Guardian was important as a signal of a window of opportunity, and so was the attention and re-framing of the issue enabled by the digital petitions gathered by actors and technical artifacts in the campaign assemblage, including crowdsourced leaders (Papacharissi and de Fatima Oliveira 2012) and hybrid advocacy organizations.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, it has become clear that rather than conceptualising this process as a battle of politicians against the media, it is more productive to understand it as actor-centred, i.e. a range of political actors trying to use the media strategically to advance their positions in intra-elite power battles (Sevenans, 2018;.…”
Section: Dynamics Of Political Agenda-setting In the Hybrid Media Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to note that the three agendas under study are not independent of one another. Research has already shown that there is a reciprocal relationship between, for example, the media agenda and the Twitter agenda of politicians (Conway et al, 2015; Conway-Silva et al, 2018; Harder et al, 2017) but also between the media agenda and the parliamentary agenda of politicians (Sevenans, 2018; Van Aelst and Vliegenthart, 2014). However, this reciprocal influence does not affect the degree of autonomy of the different agendas.…”
Section: Agenda Autonomymentioning
confidence: 99%
“…The first signal we consider is media attention. Sevenans (2018) specifies several specific tasks media signals can fulfill for parties. Media attention can reveal novel information about social problems, can reflect and influence public opinion, can create a window of opportunity to push long-held policy plans and can include frames that allow for critically assessing and targeting political opponents.…”
Section: Mass Media Signalsmentioning
confidence: 99%